2018
DOI: 10.1002/hpm.2601
|View full text |Cite
|
Sign up to set email alerts
|

Costs and efficiency of gatekeeping under varying numbers of general practitioners

Abstract: We study the relationship between gatekeeping on one hand and costs as well as efficiency on the other hand. We do this with special focus on the relative amount of general practitioners in the system when compared with all practitioners. Data collected between 2002 and 2011 by The Organization for Economic Co-operation and Development on 34 countries were analyzed. Of those, 18 countries have gatekeeping systems while 16 do not. The association between gatekeeping and health care costs was examined with regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
1
0
2
Order By: Relevance
“…Likewise, the positive association between nurse-led follow-up of people with chronic conditions and efficiency, and task-shifting from physicians to nurses in primary care is also reflected in the wider literature suggesting that substitution of physicians by nurses in primary care can have a positive effect on health outcomes and patient satisfaction, although the effect on costs, health system outcomes, and quality of life is less conclusive [ 61 64 ]. Similarly, the association of a requirement to obtain a primary care referral to specialist care with higher efficiency aligns with previous studies [ 65 , 66 ] that reported higher efficiency scores for OECD countries that had primary care gatekeeping arrangements in place.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, the positive association between nurse-led follow-up of people with chronic conditions and efficiency, and task-shifting from physicians to nurses in primary care is also reflected in the wider literature suggesting that substitution of physicians by nurses in primary care can have a positive effect on health outcomes and patient satisfaction, although the effect on costs, health system outcomes, and quality of life is less conclusive [ 61 64 ]. Similarly, the association of a requirement to obtain a primary care referral to specialist care with higher efficiency aligns with previous studies [ 65 , 66 ] that reported higher efficiency scores for OECD countries that had primary care gatekeeping arrangements in place.…”
Section: Discussionsupporting
confidence: 87%
“…Está ampliamente descrito que todo sistema sanitario con la Atención Primaria (AP) como eje central obtiene mejores resultados en términos de morbi-mortalidad 1 , reduce las desigualdades en salud y, todo ello, de forma más coste-eficiente 2 , 3 , 4 . Tanto la declaración de Alma-Ata de 1978, como la de Astaná en 2018, sitúan a la AP en el centro del sistema sanitario como estrategia para mejorar la salud mundial y definen sus valores clave: equidad, solidaridad, justicia social, salud comunitaria, educación y promoción de la salud, así como participación y autonomía de las personas y comunidades 5 , 6 .…”
Section: Introductionunclassified
“…El Sistema Nacional de Salud (SNS) español está basado en la AP como puerta de acceso 4 . No obstante, tanto la formación académica como el sistema sanitario reproducen la hegemonía del paradigma biomédico, concibiendo a la enfermedad como un fenómeno exclusivamente biológico e individual, lo que se contrapone al modelo biopsicosocial que define la AP, basado en la atención integral al paciente y en la toma de decisiones compartidas 7 , 8 .…”
Section: Introductionunclassified
“…Our findings are particularly important for other settings with a gate-keeper healthcare model where patients must first visit their primary care provider or general practitioner before being referred to speciality care, approved for tests, or prescribed new medication. This model is common in other OECD countries with public health care systems, such as Canada, the United Kingdom, Spain, and Italy (Reibling and Wendt 2012;Brekke, Nuscheler, and Straume 2007;Rotar et al 2018;Watt 1987;Blöndal and Ásgeirsdóttir 2019). As we have demonstrated in Chile, in such gatekeeper health care systems a light touch intervention such as nudging patients to attend primary care can have potentially large and meaningful impacts as it intervenes in the first step in the cascade of care.…”
Section: Discussionmentioning
confidence: 89%